Volume 2D: Turbomachinery 2016
DOI: 10.1115/gt2016-56653
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Numerical Characterization of the Suction Side Laminar Separation Bubble for a High-Lift Low Pressure Turbine Blade by Means of RANS and LES

Abstract: The scope of this work is to obtain a deep insight of the occurrence, development and evolution of the laminar separation bubble which occurs on the suction side of the high-lift T106-C low pressure turbine blade operated at correct engine Mach and Reynolds numbers. The commercial codes Numeca FINE/Turbo and FINE/Open were used for the numerical investigation of a set of three different Reynolds numbers. Two different CFD approaches, characterized by a progressively increasing level of complexity and detail in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…36 During the development of the leading-edge boundary layer, fluid particles separate and are sprayed onto the suction surface of the blade, which is associated with bubble formation in these areas. 46 Bigoni et al 47 sketched the flow structures at the leading edge, as shown in Figure 10. The figure shows that an area with intensive EGR appeared in the leading-edge boundary layer around the dividing streamline.…”
Section: Inlet Egrmentioning
confidence: 99%
“…36 During the development of the leading-edge boundary layer, fluid particles separate and are sprayed onto the suction surface of the blade, which is associated with bubble formation in these areas. 46 Bigoni et al 47 sketched the flow structures at the leading edge, as shown in Figure 10. The figure shows that an area with intensive EGR appeared in the leading-edge boundary layer around the dividing streamline.…”
Section: Inlet Egrmentioning
confidence: 99%